Chemical Thinning and Fisheye Clip for Managing Light Intensity in the Understory of Forest Restoration - Barros, Andre Junqueira; Loiola, Priscilla de Paula [UNESP]; Viani, Ricardo Augusto Gorne (Mdpi, 2023)
Research highlights: Tropical forest restoration can be supported by the production of timber species in their understory. While they may appear at odds, they can be reconciled to promote environmental conservation and services. The lack of information on the management of tropical species causes a technical constraint for timber production in the understory of restoration sites, especially given the light restrictions. This issue could be amended with the development of methods to easily manage and estimate light availability, targeting management practices that balance restoration success and productivity. Materials and Methods: We conducted this study in an area within the Atlantic Forest, Brazil, where we tested the efficiency of chemical thinning to increase light availability in the understory of a five-year-old restoration planting, aiming to increase the growth rates of desirable timber species. Moreover, we tested the viability of using hemispherical photography taken with a smartphone to assess light incidence to assist restoration management practices. We calculated the percentage of photosynthetically active radiation (PAR) using a ceptometer in four different thinning intensities and compared them to the smartphone measures using correlation analysis. Results: Chemical thinning increased light incidence in the understory, with potential impacts on timber species productivity. Light management through PAR and canopy opening were highly correlated overall, especially after three months of management and 60% of thinning intensity. Conclusions: These findings demonstrate the potential for chemical thinning as a management practice to enhance light availability in the understory of tropical forest restoration sites. Additionally, our study highlights the value of using affordable and accessible tools like smartphones and fisheye clips for the indirect assessment of light conditions to promote natural regeneration and guide forest management and timber production in tropical forest restoration.
Keywords: canopy opening; ceptometer; chemical thinning; ecological restoration; hemispherical photography